Expression of Staphylococcal Virulence Genes In Situ in Human Skin and Soft Tissue Infections - Michael S. Pulia; Jennifer Anderson; Zhan Ye; Noha S. Elsayed; Thao Le; Jacob Patitucci; Krishna Ganta; Matthew Hall; Vineet K. Singh; Sanjay K. Shukla (Antibiotics, 2022)
Background: Staphylococcus aureus, the most common pathogen in skin and soft tissue infections (SSTI), harbors many well-characterized virulence genes. However, the expression of many of them in SSTIs is unknown. In this study, S. aureus virulence genes expressed in SSTI were investigated. Methods: Fifty-three subjects presenting to the outpatient’s care and emergency departments with a purulent SSTI at two medical centers in Wisconsin, USA, were enrolled in the study. Total mRNA was extracted from the purulent or swab materials, made into cDNA and sequenced on MiSeq platform. The relative cDNA counts to gmk and identifications of the transcripts were carried out with respect to USA300 reference genome and using SAMTOOLS v.1.3 and BWA, respectively. Result: A significantly higher cDNA count was observed for many of the virulence and regulatory gene transcripts in the pus samples compared to the swab samples relative to the cDNA counts for gmk, a housekeeping gene. They were for lukS-PV (18.6 vs. 14.2), isaA (13.4 vs. 8.5), ssaA (4.8 vs. 3.1), hlgC (1.4 vs. 1.33), atl (17.7 vs. 8.33), clfA (3.9 vs. 0.83), eno (6.04 vs. 3.16), fnbA (5.93 vs. 0.33), saeS (6.3 vs. 1.33), saeR (5.4 vs. 3.33) and agrC (5.6 vs. 1.5). Conclusions: A relative increase in the transcripts of several toxins, adhesion and regulatory genes with respect to a gmk in purulent materials suggests their role in situ during SSTIs, perhaps in an orchestrated manner.